The Phenomenon of Political Movements on Social Media After the 2024 Presidential Election (A New Direction of Indonesian Democracy) - Ilham, Arifin; Junaidi, Junaidi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The 2024 Presidential Election brought new dynamics to Indonesia's democracy, with social media emerging as the primary platform for political movements. This study aims to address the research problem regarding how social media influences political participation patterns and the direction of democracy after the election. A qualitative approach with phenomenological research design was employed to explore the experiences of individuals and groups in forming and participating in social media-based political movements. Data were collected through in-depth interviews, online participatory observation, and analysis of social media posts. Manuel Castells' network society theory served as the basis for understanding the role of digital society in political interactions. The findings reveal that social media enhances inclusive political participation but also increases the risks of polarization and disinformation, which can impact the quality of democracy. The research findings indicate that social media has emerged as a new political arena, displacing the dominance of traditional actors. Influencers and buzzers act as emotional bridges between political policies and public perception, while civil society groups leverage digital platforms for advocacy and democratic oversight.